Bowl-shaped Tröger's bases and their recognition properties. Issue 70 (9th August 2016) - Mosca, Lorenzo; Čejka, Jan; Dolenský, Bohumil; Havlík, Martin; Jakubek, Milan; Kaplánek, Robert; Král, Vladimír; Anzenbacher, Pavel
Abstract : The electron rich bowl-shaped tris-Tröger bases calix-1 and calix-2 display fluorescence quenching in presence of nitroaromatic analytes. Crystal structures show the formation of inclusion complexes. Abstract : The tris-Tröger's bases (TBs) are electron-rich fluorescent concave receptors due to the incorporation of naphthalene or triphenylene moieties (calix-1 and calix-2 ). The structures of the TBs were studied using SXRD to reveal the propensity to bind nitroaromatics. Titration with explosive-related nitro-compounds suggests that the TBs may be used for sensing explosives.